2004
DOI: 10.17660/actahortic.2004.663.13
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Pathogenicity of Venturia Inaequalis in Europe

Abstract: In INTRODUCTIONThe overall objective of the DARE project was to improve the knowledge on the genomic organisation of resistance factors in apple, and to select cultivars with a broad spectrum of resistance. Hence, an important topic of the project was the study of the variability and the geographical distribution of the pathogenicity of V. inaequalis in Europe, with a strong focus on partial resistances.However, the Vf gene was given special attention because it is the main source of scab resistance used in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…Plot P2 was grown with a mixture of different hybrid forms, giving 25% of plants susceptible to race 710, one third of which contributed to parasitic multiplication. Compared with plot P1, and with few infected plants, it is reasonable to suggest that isolates with a high sporulation capacity could have been favored and may have caused the secondary infections shown by 20% of infested plants in this plot between 2001and 2004(Tourvieille de Labrouhe et al 2010. These secondary infections contributed to the stock of inoculum which may explain why strains isolated from this plot showed a significantly higher sporulation density.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Plot P2 was grown with a mixture of different hybrid forms, giving 25% of plants susceptible to race 710, one third of which contributed to parasitic multiplication. Compared with plot P1, and with few infected plants, it is reasonable to suggest that isolates with a high sporulation capacity could have been favored and may have caused the secondary infections shown by 20% of infested plants in this plot between 2001and 2004(Tourvieille de Labrouhe et al 2010. These secondary infections contributed to the stock of inoculum which may explain why strains isolated from this plot showed a significantly higher sporulation density.…”
Section: Discussionmentioning
confidence: 90%
“…nicotianae. In the pathosystem Venturia inaelalie/apple, Parisi et al (2004) found that virulent strains taken from cultivars carrying vertical resistance genes were highly aggressive. Since the four sunflower hybrids in the present study were isogenic except for their Pl genes, it is probable to consider that selection pressure was mainly applied on criteria linked to virulence (Tourvieille de Labrouhe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They named it Vfh, but they did not map it. According to Parisi et al (2004), EU-NL-24 can sporulate on M. floribunda 821. This indicates that the Vfh gene is not the same as the Vd3 gene.…”
Section: Vd3 Is a New Apple Scab Resistance Genementioning
confidence: 99%
“…Results on monoconidial strains (Table 1) can partially be compared with those obtained by Parisi et al (2004) on a range of differential hosts -'Gala', 'Golden Delicious', 'Prima', Malus floribunda 821, 'Fiesta', 'TN10-8', 'Discovery', 'Durello di Forli' -inoculated with strains EU-B-04, EU-D-42, EU-NL-05, EU-NL-19 and EU-NL-24. Few discrepancies can be found between the two experiments: 'Golden Delicious'/EU-NL-05; 'Discovery'/EU-D-42 and 'TN10-8'/EU-NL-19; some other slight quantitative variations can also be found.…”
Section: Inoculum Characterizationmentioning
confidence: 99%